(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Politeness strategies has been first proposed by Brown and Levinson in 1987, since then, many studies have been dealing with these strategies, primarily in an informal classroom basis since the formal classroom basis is limited within curriculum designed by the government. This study is related to the interactions that are taken place in the governmental school classrooms between teacher and student or students through mixed-method research design, the recoded data were analyzed according to Brown and Levinson’s Politeness strategies. The researcher includes all the four types of politeness strategy in her study; two teachers (male and female) were included in this study, they both were teaching the fourth preparatory grade with two groups of student for each teacher. The researcher had found that: gender is an effective factor in choosing different strategies by the teacher, since the same teacher may use a completely different strategy with male than female students. Both teachers used different strategies with both groups of students, but their strategies were different and multiple.